Analisis Pengaruh Kewenangan Penangkapan Tanpa Surat Penahanan Menurut KUHP Ditinjau dari Teori Kewenangan Diskresi - Putri, Yuliani Finaly (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Police forces often use discretion in warrantless arrests, especially when there is deemed to be a direct threat to national security. Purpose of this writing to analyze and provide a comprehensive description of the influence of the discretionary authority of law enforcement officers in making arrests without a warrant and its impact on the rights of suspects. Using normative juridical methods it is used to analyze the applicable legal provisions related to arrest without a warrant of detention, including the use of discretion by law enforcement officers. The importance of arrest warrants in law enforcement asserts that arrest warrants are essential elements that serve to ensure that arrests are made according to legal procedures. Although law enforcement officers have discretionary authority, legal limits such as those provided for in the code of criminal procedure must still be observed to prevent abuse of authority.